Instilling Islamic Educational Values in Shaping Student Character at Vocational High School (SMK) Patria Gadingrejo - Ardian Firdaus (Assyfa Journal of Islamic Studies, 2026)
This study aims to analyze the planning, implementation, and evaluation of instilling Islamic educational values in shaping student character at Vocational High School (SMK) Patria Gadingrejo. The background of this research is the concerning moral decline among students, characterized by low discipline, honesty, mutual respect, and religious behavior. This research employs a qualitative approach with a case study method. Data collection techniques include observation, in-depth interviews, and documentation involving the principal, Islamic Religious Education (PAI) teachers, and parents of students. The informants were selected purposively based on their direct involvement in the character education process. Data analysis was conducted through data reduction, data presentation, and conclusion drawing. The results of the study indicate that the planning of instilling Islamic educational values is carried out through teacher and committee meetings, preparation of the Character Strengthening Education (PPK) program, development of PAI teaching modules, and preparation of competent PAI teachers. The implementation is conducted through habituation activities such as praying before and after learning, reading and memorizing the Qur'an, performing Dhuha and Dzuhur prayers in congregation, infaq and charity, as well as the 3S culture (smile, greet, and respect). Evaluation is conducted through authentic assessment, criterion-referenced assessment, and reporting of learning outcomes. This study concludes that the instillation of Islamic educational values at SMK Patria Gadingrejo has been implemented through an integrated approach between planning, implementation, and evaluation, resulting in students with religious character, good morals, and obedience in worship.